A literature review of bench top and pilot lead corrosion assessment studies. Issue 2 (24th March 2023) - Devine, Christina; Triantafyllidou, Simoni
Abstract: Bench top and pilot lead corrosion studies are gaining more interest, considering revisions and upcoming improvements to the Lead and Copper Rule. This literature review identified studies ranging from simpler month(s)‐long bench top dump‐and‐fill stagnant water tests (coupon tests/standing pipe tests) to more complicated year(s)‐long intermittent flow pilot studies (recirculating pipe loops/once through pipe rigs). With increasing complexity in design and operation, studies more closely approximated real plumbing conditions (e.g., by incorporating harvested lead pipes and intermittent flow regimes) at increased cost, footprint, and duration. Comparison of bench top and pilot designs (in terms of lead test piece age/dimensions/configuration/replicates, study duration, sample collection, and other factors) can assist drinking water utilities, consultants, academics, and others to select a design that matches their needs and constraints. No matter the choice, surrogate systems cannot replace actual system water testing and are best complemented by other corrosion assessment tools.